THE EFFECT OF COATING FORMULATION AND STORAGE PERIODS ON THE QUALITY AND GROWTH OF TSS (TRUE SHALLOT SEED) ONION (Allium cepa L.) - Riesdewanti, Ervira (Yayasan Education and Social Center, 2024)
Efforts to improve the provision of quality TSS seeds are by doing seed coating. Seed coating is a seed coating technique using a coating agent that aims to maintain seed viability. Vigor tss seeds often decrease due to the length of time the seeds are stored. So that the length of seed storage until the seed will affect the quality of the seeds produced. Seed coating on TSS seeds and determining the right storage duration are expected to be able to maintain the quality of TSS seeds. The research will be carried out from January to April 2024 in the Laboratory, Green House, and UPT land. Development of Rice and Palawija Seeds, Randuagung, Singosari, Malang, East Java. This study was prepared using a factorial Complete Randomized Design (RAL) that was repeated four times. The first factor is a coating material with 4 levels (without coating, CMC 1.5% + Humic Acid 0.6% + Liquid Smoke 0.5% + Gypsum 10 grams, CMC 1.75% + Humic Acid 0.6% + Liquid Smoke 0.5% + Gypsum 10 grams and CMC 2% + Humic Acid 0.6% + Liquid Smoke 0.5% + Gypsum 10 grams) and the second factor is the storage periods with 3 levels (no storage, storage periods 2 weeks and storage periods 4 weeks). The results showed that the combination of CMC coating formulation 1.5% + Humic Acid 0.6% + Liquid Smoke 0.5% + Gypsum 10 grams with a storage period of 4 weeks (F1M4) is the best combination for coating onion TSS seeds. The combination differs markedly from growth speed, coarseness, germination rate, vigor index, plant length, and number of leaves